Implementation of Centroid Clustering Method for Industrial Clusterization in Regencies and Cities in Maluku Province - M. Y. Matdoan; Rahmi Fadhilah; N. S. Laamena; Dinda Ayu Safira; S. B. Loklomin (Pattimura University, 2024)
The industrial sector has a vital role in economic development. In addition to increasing state revenue, the industrial sector can also provide business opportunities that make a positive contribution to efforts to equalize community welfare. The limited employment opportunities available in Maluku Province need to be balanced with the increase in the labor force, which significantly impacts the high unemployment. Basically, the high unemployment rate will significantly impact economic development, which aims to improve the standard of living of the people in Maluku Province. Centroid Linkage is the average of all objects in the cluster, and the distance. The distance between the cluster centroids is what separates two clusters. Cluster centroid is the center value of observations on variables in a set of cluster variables. The purpose of this research is to cluster the distribution of industries in regencies and cities in Maluku Province using data from BPS Maluku Province. This study obtained the results that there are 3 clusters formed in the clusterization of industry in regencies and cities in Maluku Province, namely cluster 1 consisting of Tanimbar Islands Regency. Cluster 2 consists of Buru, South Buru, West Seram, East Seram, Central Maluku, Tual City, Southeast Maluku, and Aru Islands Regency. Furthermore, Cluster 3 consists of Ambon City and Southwest Maluku.